Psychological and Livelihood Impacts of COVID-19 on Bangladeshi Lower Income People. (January 2021) - Paul, Alak; Nath, Tapan Kumar; Mahanta, Janardan; Sultana, Naznin Nahar; Kayes, A. S. M. Imrul; Noon, Sharifa Jahan; Jabed, Md. Akib; Podder, Sumana; Paul, Sujat
The objective of this research is to understand the psychological and livelihood-related impacts of coronavirus disease 2019 (COVID-19) on Bangladeshi lower income group people who depend on daily earnings for their living. Following the convenience sampling method, 576 respondents were interviewed for quantitative data and 30 in-depth interviews for qualitative information in several districts of Bangladesh. To 94.1% respondents, livelihood has been affected by the COVID-19 outbreak with an overall score of 3.20 ± 0.77 on a 4-point Likert-type scale. In comparison to unemployed respondents, daily workers have been hardly affected by the COVID-19 outbreak (odds ratio [OR] = 7.957; P < .01), and so they are going outside more frequently in search of jobs (OR = 9.984, P < .01). Due to fear of COVID-19 infection and lack of livelihood means, respondents (76.6%) have been stressed out (overall score 3.19 ± 0.81 on a 4-point Likert-type scale), and those working in industries (OR = 5.818, P < .01), farmers (OR = 3.029, P < .05), and day laborers (OR = 2.651, P < .05) have been highly stressed.